Benchmarking Public Procurement 2017 : Assessing Public Procurement Regulatory Systems in 180 Economies - World Bank (World Bank, Washington, DC, 2019)
Despite the importance of the public procurement market, little effort has been made to systematically and consistently collect reliable statistics on a number of critical dimensions. To date, no attempt has been made to collect comparable statistics on the size of public procurement in economies around the world. While data are publicly available for High-income economies, for the rest of the world, data and studies are scarce. However, public procurement is as important in developing countries as it is in advanced economies. Governments in developing countries are significant purchasers of good and services, and these markets represent huge opportunities to enhance competition and development. Low-income countries have the highest share of publicprocurement in their economies, at 14.5 percent of GDP, followed by upper-middle income countries, at 13.6 percent, as data from government sources or international development institutions indicate. International statistics fall short in systematically and comparably capturing a number of other important dimensions of public procurement, including the regulatory and legal environment, risks and costs, quality and efficiency of service delivery, transparency and competition.